Multi-User Gesture Recognition with Radar Technology - Ninos, Alexandros (Karlsruher Forschungsberichte aus dem Institut für Hochfrequenztechnik und Elektronik, 2022)
The aim of this work is the development of a Radar system for consumer applications. It is capable of tracking multiple people in a room and offers a touchless human-machine interface for purposes that range from entertainment to hygiene.